PENGARUH MODAL INTELEKTUAL TERHADAP ABNORMAL RETURN SAHAM, TRADING VOLUME ACTIVITY DAN KINERJA KEUANGAN (STUDI PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2015-2021). - Dewanda, Adrian; Anggraeni, Puspitasari Wahyu (Contemporary Studies in Economic, Finance and Banking, 2022)
This study aims to determine the effect of intellectual capital on abnormal returns, trading volume activity ROA, and ROE in banking companies in 2015-2021. The types of data and data sources used in this study are secondary data obtained from the annual reports of banking companies from 2015-2021. This study uses a sample of 8 banking companies from 2015-2021. Sampling using purposive sampling technique. The data analysis used is descriptive analysis, canonical correlation test, classical assumption test, multiple regression test, and hypothesis testing. From the test results on the four variables, it can be concluded that the intellectual capital variable has a positive effect on the abnormal return, trading volume activity, ROA, and ROE variables. And also the intellectual capital variable has a close relationship with the ROA and ROE variables. These results indicate that by increasing the value of intellectual capital, banking companies can have a competitive advantage so that they can compete with competitors.